Combined treatment with memantine and galantamine‐CR compared with galantamine‐CR only in antidementia drug naïve patients with mild‐to‐moderate Alzheimer's disease. Issue 3 (19th October 2015) - Peters, Oliver; Fuentes, Manuel; Joachim, Lisa Katharina; Jessen, Frank; Luckhaus, Christian; Kornhuber, Johannes; Pantel, Johannes; Hüll, Michael; Schmidtke, Klaus; Rüther, Eckart; Möller, Hans‐Jürgen; Kurz, Alexander; et al.
Abstract: Introduction: Several studies have tested the N‐methyl‐D‐aspartate–receptor antagonist memantine as an add‐on to pre‐existing treatment with acetylcholinesterase inhibitors. The objective of this study was to evaluate the efficacy and safety of a combined memantine and galantamine‐CR de novo regimen compared with galantamine‐CR only treatment in never treated patients with mild‐to‐moderate Alzheimer's disease (AD). Methods: Antidementia drug–naïve participants (n = 232) with probable, mild‐to‐moderate AD, and mini‐mental state examination scores between 15 and 26 (inclusive) were randomized to receive either 20 mg/day memantine plus 24 mg/day galantamine‐CR or 24 mg/day galantamine‐CR plus placebo in a 52‐week, prospective, double‐blind, controlled trial. The primary outcome measurement was the change on the Alzheimer's disease assessment scale‐cognition score. Secondary measures comprised the Alzheimer's Disease Cooperative Study‐activities of daily living inventory and the clinical dementia rating. Results: At the end of the trial, there were no statistically significant differences between the galantamine‐CR/memantine combination and galantamine‐CR only group in primary and secondary outcome measurements. The incidence and the severity of adverse events were similar between the groups. Discussion: In this trial, memantine in combination with galantamine‐CR did not show an advantage with respect to cognition, function, and behavior in previously never treated patients with mild‐to‐moderate AD. There were no significant differences in tolerability and safety between the groups. Thus, a de novo combination treatment results in no significant improvement in disease progression (current controlled trials number: NCT01921972 ).